The Effectiveness Test of Bangun-Bangun Leaves Extract (Plecthranthus Ambonicus) Against Streptococcus Pyogenes and Salmonella Typhi Bacteria - Windi Anggriani; Stella Retta Marina; Ayu Hasanah; OK Yulizal (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background Bangun-bangun leaves (Plectranthus amboinicus) are part of theLamiaceae family. (1) (1) Bangun-bangun leaves have a characteristic aromatic leavesaroma used as a medicinal plant (2). According to research conducted by (Dalimunthe et al., 2016) to find the use of this plant as an antibacterial because it contains compounds such as flavonoids, tannins, tripenoids, saponins, and essential oils. On the bangun-bangun leaves there is carvacrol, which is an essential component that has antibacterial activity in positive or negative gram bacteria. streptococcus pyogenes bacteria are vectors of suppurative infectious diseases and other diseases such as pharyngitis. While salmonella typhi bacteria is a vector of the disease which is usually called typhus and the medical language is typhoid fever. The purpose of this study was to determine that the bacteria salmonella typhi and streptococcus pyogenens can be inhibited by the leaves extract. The benefit of this research is to increase public understanding and knowledge in the use of bangun-bangun leaves. The method used in this study is an experimental method and post test only controlled group design. For the concentration used, namely 5%, 10%, 15%, 20%, 25% and this strength test is done by inserting the extract into a petri dish that has a bacterial culture. Data processing uses one-way ANOVA with the aim of comparing each variable. To see the extract against bacteria. The results showed that there were variations in the diameter of the inhibition zone formed by the concentration of the extract. And the most effective concentration to inhibit streptococcus pyogenes bacteria was a concentration of 25%, the inhibition zone diameter was 19.5mm, while salmonella typhi bacteria had a concentration of 25% and the inhibition zone diameter was 37.7m.